FAKTOR-FAKTOR YANG MEMPENGARUHI DAYA SAING UMKM DI KABUPATEN REMBANG - DIAN ANITA SARI; Syaiko Rosyidi (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2018)
The role of UMKM to the economic development of a region is very important, as well as with Rembang regency. Strengthening the competitiveness of UMKM become strategic effort in winning the competition between UMKM in a region. Therefore, finding the factors that affect the competitiveness of UMKM become necessary for the development of UMKM.The purpose of this study is to determine the factors that affect UMKM in Rembang. Competitiveness factors are measured using product advantages, human resources, and product marketing using IT. The sample in this research is the leading sector of UMKM in Rembang such as Batik Lasem, Processed Fish, and Furniture. Sampling method using purposive sampling with the number of research respondents is 100 respondents. Data collection techniques with interviews, observations, and questionnaires. Data analysis method by conducting instrument test (validity test and reliability test), data analysis technique (multiple linear regression test, test of determination, and t-test).Validity and reliability test is done with 30 respondents which are all valid and reliable results. Result of t-test proves that independent variable consisting of product superiority, human resources, and product marketing by using IT have a significant positive effect to competitiveness of UMKM. In F test, get result of significance value smaller than 0,05. This proves that simultaneously the independent variables affect the dependent variable. Determination test proves that product superiority, human resources, and marketing of products using IT affect the competitiveness of 56%, while the rest is influenced by factors outside the independent variable in this study. Keywords: UMKM, Competitiveness, Featured Products